Characterization of α-Cyclodextrin Glucanotransferase from Bacillus licheniformis - N., Jamil; Rohaida, Che Man; Shalyda, Md Shaarani; Siti Zubaidah, Sulaiman; Siti Kholijah, Abdul Mudalip; Zatul Iffah, Mohd Arshad (Informatics Publishing Limited, 2017)
Objectives: Cyclodextrin glucanotransferase (CGTase) is a multifunctional industrial enzyme, which undergoes cyclization reaction to converts starch into Cyclodextrin (CD). Due to their potential properties, CDs had been discovered to have numerous application in food industries, pharmaceutical, agriculture and also environmental engineering. To improve the production of cyclodextrin (CD) in the future, characterization of α-CGTase on the effect of operating conditions was investigated. Methods/Statistical Analysis: The α-CGTase from Bacillus licheniformis was characterized by examining their cyclization activity. The enzymatic activity of the enzyme towards the temperature and pH was determined by methyl orange method. Findings: The enzyme was estimated to be 70 kDa by the gel electrophoresis. The cyclization activity of α-CGTase was highest at a temperature of 40°C and pH 6.0. The α-CGTase enzyme was able to extend its thermostability up to 60°C with pH stability between pH 6.0 and pH 8.0. Application/Improvements: High production of CD is expected to obtain by using the optimal conditions which in turn may be beneficial for the industrial purpose.